The Corporation, Competition, and the Invisible Hand - Marris, Robin; Mueller, Dennis C. (Journal of Economic Literature, 2016)
FEW WOULD DISAGREE that Adam Smith's invisible-hand theorem is the heart of the economist's Weltanschauung. Ask whether trade barriers should be lowered, the spread of multinational corporations restrained, oil prices deregulated, cartels dissolved, or more fundamentally whether a market-based capitalist system is economically superior to a state-run socialist system, and economists almost certainly will begin to answer the question by trying to apply the theorem. Every student knows that the theorem depends on the assumption of atomistic competition, which in turn assumes that the system is decentralized and that no competitor is large relatively to others. There is another crucial assumption, however, that is often ignored and usually underemphasized, namely that all competition is price competition. In reality one of the most distinctive features of capitalism-one that is most often raised in lay discussions of its merits and demerits-is the prevalence of other forms of competition, such as competition in research, development, and advertising; competition to obtain and hold monopoly; and competition for corporate growth. These various forms of competition, we shall aim to show, are not clearly analogous with the theory of price competition: more non-price competition, rather than less, is not necessarily Pareto optimal. Self-evidently, the production side of a market economy is decentralized only to a limited degree, i.e., to the level of a decision-making unit composed of more than one human. Such a unit-playing Neuron to the Invisible Hand-is typically called a firm. It is in fact a team. Rather than remaining small, firms are in practice composed of any number of individuals from a handful on to half a million. Some